A survey of methods used for assessing the performance of diesel locomotives - Juršėnas, Vidmantas; Vaičiūnas, Gediminas (Transport, 2007)
The present paper is aimed at evaluating the methods used for determining the performance of Diesel locomotives. Therefore, two main approaches to assessing the locomotive performance can be distinguished: a method based on individual indicators; a method based on an integrated indicator. The analysis of the available methods for complex evaluation of the locomotive condition has shown that overall performance of the locomotive can be described by a dimensionless indicator. In determining the state of Diesel locomotives, researchers rely on the criteria commonly used in assessing the performance of any machine. They are as follows: technical, economical, functional (operational).First Published Online: 27 Oct 2010